(3WHbGJ GdTGaYjIs - (3YHO GdhgGH Hf Ydj Hf YHO GdcGaj GdSHcj, CHh fUQ , JGL GdOjf , J (B771 (3g` s; (3JGL GdOjf GdSHcj , CHh fUQ,J (B771 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3eHJhQ hJHOC HJQLeI eMeO Hf CMeO Hf MeOGf , GdeJhaj SfI JSY hJSYjf hKdGKeGFI s
(3BNQgG (B:s
(3hEdi gfG GfJgi gPG GdoeNJUQ faY Gddg Hg hLYdg NGdUkG dhLgg GdcQje bGd eDdag TjNfG hCSJGPfG aQZJ ef gPG GdoeUfa ai djdI GdKGdK hGdYTQjf ef Pj GdbYOI SfI CQHY hNeSjf hSHYeGFI HOeTb YeQgG Gddg JYGdi s
(3GfXQ Qbe (B314s
(3Qbe (B1127 (3JGQjNs
(3hQOJ CjVkG JMJ YfhGf (B"(3GdedJbW ef WHbGJ GdTGaYjI GdcHQi hGdhSWi(B" (3HQbe (B2068" (3JGQjNs
(3fSNI SGOSI s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdJGQjNs